Application and development of CORD - Wei ZHOU; Xiongyan TANG (Dianxin kexue)
CORD open source project provides one implementation reference of unified access edge cloud.On the basis of analysis of influence of CORD project on the existing CO and DC,the core architecture and software stack of CORD were studied.Meanwhile,the integrated reference solution of 5G-oriented mobile scenario and performance analysis was also analyzed.Finally,the reference solution to integrate CORD with other open source was given.